Moderating Role of Trust in Relationship between Team Diversity and Conflict: Empirical Evidence from Health Sector - Terresa, Maria; Ahmad, Ishtiaq (Archives of Business Research, 2017)
Purpose: The purpose of this study was to investigate the impact of diversity on conflict. Moreover, it also scrutinized the relationships between intra-team trust and conflict among members of a team. In addition to it, this research also measured the moderating role of trust on relationship between diversity and conflict among team members. Methodology: Data was collected using personally administered questionnaires from 61 teams which include 377 respondents working in four public sector hospitals in Pakistan which were selected using simple random sampling technique. Results: Results revealed that teams composed of diverse individuals have more chances of conflict, but if the level of trust among team members is high, it reduces the magnitude of conflict in a team. Moreover, results also lead to an interesting finding that in presence of trust the conflict becomes more functional and less harmful. Originality: This is first study in Pakistani context which explores the potential relevance of trust, diversity and conflict in healthcare industry. Keywords: Diversity; Conflict; Trust; Teams; Healthcare Industry; Pakistan